Ecological Pressure and Biodiversity Conservation in Protected Areas: MDS Approach on Road Development in TN Babul, Indonesia - Safri Arif; Harsuko Riniwati; Gatot Ciptadi; Hasnidar; Reny Tiarantika (Research in Ecology, 2025)
Infrastructure development within protected areas has become a critical concern in biodiversity conservation, particularly in ecologically sensitive regions like Bantimurung Bulusaraung National Park (TN Babul), Indonesia. This study aims to evaluate the ecological, social, economic, institutional, and infrastructural sustainability of the Maros–Watampone road corridor that crosses TN Babul. Using a qualitative descriptive design, the research employed the Multidimensional Scaling (MDS) method supported by leverage and Monte Carlo analysis. Data were gathered from key stakeholders through purposive sampling and analyzed based on sustainability attributes across five dimensions. The findings reveal that environmental, institutional, and infrastructure dimensions scored in the "less sustainable" category, indicating high ecological risk and governance gaps. In contrast, economic and social dimensions were moderately sustainable, reflecting emerging opportunities for inclusive growth. Sensitive attributes influencing sustainability include habitat fragmentation, road design, governance coordination, and community participation. The study concludes that balancing development with conservation requires integrated, multi-stakeholder strategies and targeted interventions that address the most vulnerable sustainability dimensions.